Responsabilidade civil do árbitro no direito brasileiro - Sanches, Matheus Soubhia (2021)
This paper analyzes the civil liability institute of the arbitrator according to the Brazilian legal system. Emphasizing the importance of the arbitrator for the development of the arbitration and going through the analysis of the duties and rights that this judge has, as well as the legal nature of the arbitration, this work seeks to define the extent of the civil liability of the arbitrators, as well as in what situations he could be held responsible. In this work, there is a historical evolution of the civil liability institute, as well as the current concept and the rules applicable in the Brazilian legal system, as well as the analysis of each of the requirements to be observed in the different civil liability regimes. Going through an analysis of the Arbitration Law and the standards of the main arbitral institutions in the country, it was found that there is a gap, which must be filled by the Brazilian Courts according to the peculiarity of the existing legal relationship between the reports and the parties to the proceedings arbitration, which even has consequences in relation to the statute of limitations and the initial term of default interest in the event of a conviction. For purposes of comparison, a brief analysis of the possibility of civil liability of resources in different countries was also brought up, as well as a parallel was drawn between the activity performed by resources and state judges, standing out mainly as their differences. Everything to conclude that the arbitrator responds civilly according to the function. In other words, taking into account the legal nature of arbitration, a judgmental activity involves two main pillars: the contract and the jurisdiction